An Assistance of Scientific Writing in Preparation Olimpiade Sains Tarakanita Nasional (Ostarnas) Competition - Tresiana Sari Diah Utami; Katarina Retno Triwidayati (International Journal of Community Engagement Payungi, 2022)
This dedication is titled Assistance in Writing Scientific Work in the Context of Preparation for the Olimpiade Sains Tarakanita Nasional (Ostranas) Competition. The targets and outcomes in this activity are participants writing Tarakanita scientific papers throughout Indonesia representing Lahat, able to write scientific papers that can be represented in Ostranas This training activity is a form of guiding the writing of scientific papers to be included in Ostranas. There are several methods used in community service activities at St. Yoseph Lahat include: 1) The method of discussion, finding and solving problems in writing scientific papers; 2) Assignment method, assignment in completing writing scientific papers according to agreed targets; 3). Presentation method, participants simulate the presentation of scientific papers. The results of this activity are in the form of a better understanding obtained by educators and student representatives from the Tarakanita Foundation, Lahata in writing scientific papers. In addition, for educators who were representatives of scientific writing writing competitions, they won second place in the entire Tarakanita Foundation in Indonesia